Illegal migrant Basotho women in South Africa: Exposure to vulnerability in domestic services - Mosiuoa B. Makhata (AOSIS, 2021)
The illegal migration of Basotho women to South Africa in order to render domestic service is alarming because they are subjected to harsh treatment. This is a pastoral and theological concern for the church. As migrants, their struggle begins from the household circumstances that often force them to leave and seek job opportunities undocumented or without following prescribed migration procedures. They are then subjected to migration processes and procedures: for example, corruption and bribery by migration officers and illegal dealers (lirurubele). The working and living conditions in South Africa are often unconducive for illegal migrants. As economic and illegal migrants, they are often considered as lesser by prejudiced employers who treat them inhumanely. Accessing essential services also imposes a significant threat to their lives.